TRANSMISI KEBIJAKAN MONETER DI INDONESIA - Rini Dwi Astuti; Sri Rahayu Budi Hastuti (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The use of the BI 7 days repo rate as a new benchmark rate replacing the BI rate, raises hopes that the transmission of monetary policy in Indonesia can run faster and more effectively. This study uses monthly time series data for the period August 2016-December 2018, using the Vector Autoregression (VAR) analysis. The results show that the transmission of monetary policy through the interest rate and asset price channels has been effective, while the transmission of monetary policy through the exchange rate channel has not been effective in driving economic growth in Indonesia. The decline in the benchmark interest rate can be responded quickly by interbank money market interest rates, banking interest rates, stock prices, and output. The exchange rate can also respond quickly to changes in interest rates, but changes in the exchange rate have not been able to influence net exports and increase output.